The Effect Of Leadership And Work Motivation On Employee Performance Of The Tulang Bawang Regency Agriculture Office - Septia, Ira Pria; Josiah, Trisnowati (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
In the era of globalization, government organizations must achieve short- and long-term goals through effective human resource management (HRM). Human resources are crucial assets that require fair treatment to maximize employee performance, which can be measured through indicators such as quality, quantity, and timeliness. Employee performance is influenced by leadership and work motivation. However, interviews at the Agriculture Office of Tulang Bawang Regency revealed that the current leadership style is not open enough, negatively impacting employee motivation and performance. Data indicates issues with discipline and low performance. Therefore, management needs to understand the motivational factors and create a supportive work environment to achieve organizational goals. This research aims to explore the influence of leadership and work motivation on employee performance at the Agriculture Office of Tulang Bawang Regency. This study will be conducted at the Agriculture Office of Tulang Bawang Regency from May to July 2024, using a descriptive quantitative approach. The research aims to systematically and accurately describe the facts and characteristics of a specific population. The population consists of 85 employees, with a sample of 83 employees, excluding the researcher and management. The variables used in the study include independent variables: Leadership Style (X1) and Work Motivation (X2), and the dependent variable: Employee Performance (Y), which is influenced by both independent variables. Based on data analysis and hypothesis testing, it can be concluded that both factors, Leadership (X1) and Work Motivation (X2), significantly affect Employee Performance (Y) at the Agriculture Office of Tulang Bawang Regency. Leadership contributes 21.2% to employee performance, while Work Motivation accounts for 21.7%. Overall, both Leadership and Work Motivation simultaneously influence 47.1% of employee performance at the institution.